2010
DOI: 10.1002/elan.200900634
|View full text |Cite
|
Sign up to set email alerts
|

A Nitrite Biosensor Based on Coimmobilization of Nitrite Reductase and Viologen‐Modified Polysiloxane on Glassy Carbon Electrode

Abstract: Copper containing nitrite reductase (Cu-NiR) and viologen-modified sulfonated polyaminopropylsiloxane (PAPS-SO 3 H-V) were co-immobilized on glassy carbon electrode (GCE) by hydrophilic polyurethane (HPU) drop-coating, and the electrode was tested as a reagentless electrochemical biosensor for nitrite detection. The newly synthesized PAPS-SO 3 H-V as an electron transfer (ET) mediator between electrode and NiR was effective, and could be effectively immobilized in HPU membrane. The NiR and PAPS-SO 3 H-V co-imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
6
10
0
Order By: Relevance
“…This pH profile is in accordance with that we reported previously [17,22], and this optimal pH is also very comparable to those for free Cu-NiRs purified from different sources, generally at pH 6.0−6.2 [25,30,31]. On the other hand, it was reported that the solubility transition point of chitosan is ∼6.3 [3942], and this may be partially responsible for the sharp decreases of response in the 6.5−8.0 pH range.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…This pH profile is in accordance with that we reported previously [17,22], and this optimal pH is also very comparable to those for free Cu-NiRs purified from different sources, generally at pH 6.0−6.2 [25,30,31]. On the other hand, it was reported that the solubility transition point of chitosan is ∼6.3 [3942], and this may be partially responsible for the sharp decreases of response in the 6.5−8.0 pH range.…”
Section: Resultssupporting
confidence: 94%
“…Stable successive CV scans showing ΔE p = 0.159 V and i p,a/ i p,c = 0.657 were obtained. A similar result was also obtained in the case where NiR and PAPS-V were co-immobilized on a GCE by drop-coating of HPU [22]. Figure 5 shows CVs recorded with the co-immobilized NiR and CHIT-V GCE at a scan rate of 0.002 V/s.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations